Temperature data acquisition for material performance of instrument panel (IP) in automotive applications - Paijan, Lailatul Harina; Anuar, Liza; Mamat, Mohd Fauzi (Universiti Malaysia Perlis, 2024)
The thermal heat inside the interior vehicle is the main concern to provide a comfortable environment for the passengers. Experimental studies were performed in the laboratory and field tests to study the behaviour of the temperature data acquisition in these two conditions. The material characterization analysis used in this work is Differential Scanning Calorimetry (DSC) and Thermogravimetric analysis (TGA). This study is important to investigate the thermal degradation of polymeric materials and determine the material purity used in the automotive components. The temperature measurements were recorded for the selected small component on the Instrument Panel (IP)system that exposed to the hot sun. The results show that the maximum temperature during laboratory and field tests achieved 108.33 °C and 78.2 °C at the IP meter combination, respectively. The maximum temperature achieved for each component on the IP system for both tests has shown that the material can withstand heat resistance during the thermal test in laboratory and field exposure. The temperature difference between these two tests is below 50 %. It was demonstrated that the heat resistance of the material for the IP component is compatible and relevant to automotive applications. The material characterization also revealed that the material used for ABS material on the air outlet and switch centre in the IP system was the virgin material without containing any recycled material. The temperature variations were recorded for the analysis of failure regarding heat factors in Malaysia. The data is necessary to determine whether the temperature in actual service greatly affects the problem of the component. In addition, it would be beneficial for design and material selection for interior automotive applications.